Preventive cardiology advances in the 2021 AHA/ACC chest pain guideline - Rhanderson Cardoso; Leslee J. Shaw; Roger S. Blumenthal; Khurram Nasir; Richard Ferraro; David J. Maron; Michael J. Blaha; Martha Gulati; Deepak L. Bhatt; Ron Blankstein (Elsevier, 2022)
A core principle of the 2021 AHA/ACC/ASE/CHEST/SAEM/SCCT/SCMR Chest Pain Guideline is the importance of preventive therapies among patients with nonobstructive or obstructive coronary artery disease (CAD). Accordingly, this editorial provides unique insights that emphasize the role of preventive cardiology throughout the new guideline. For the first time, CAD was defined to also include nonobstructive plaque. This definition was based on the fact that individuals who have nonobstructive plaque are at an increased risk of atherosclerotic events compared with those who do not. Herein, we highlight guideline recommendations related to the diagnosis and management of nonobstructive CAD. We also highlight recommendations which emphasize the importance of preventive therapies. Adoption of these recommendations have the potential to lead to enhanced preventive therapies and improve patient outcomes.